2003
DOI: 10.1097/01.ta.0000037095.83469.4c
|View full text |Cite
|
Sign up to set email alerts
|

Elderly Trauma Patients with Rib Fractures Are at Greater Risk of Death and Pneumonia

Abstract: Despite lower indices of injury severity, even after taking account of comorbidities, mortality was significantly increased in elderly patients admitted to a trauma center with rib fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
237
0
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 332 publications
(255 citation statements)
references
References 22 publications
9
237
0
9
Order By: Relevance
“…Travmatik yaralanmalar %10-66 sıklıkta kosta fraktürleri ile sonuçlanır. 12 Çocuklarda travma sonrası kosta kırığı, kostaların esnekliği ve yumuşaklığı nedeniyle nadirdir; özel-likle üçüncü dekat sonrası travmaya bağlı kosta kırığı insidansı artar.…”
Section: Patoloji̇k Bulgular Travma Ile İlişkili Lezyonlarunclassified
“…Travmatik yaralanmalar %10-66 sıklıkta kosta fraktürleri ile sonuçlanır. 12 Çocuklarda travma sonrası kosta kırığı, kostaların esnekliği ve yumuşaklığı nedeniyle nadirdir; özel-likle üçüncü dekat sonrası travmaya bağlı kosta kırığı insidansı artar.…”
Section: Patoloji̇k Bulgular Travma Ile İlişkili Lezyonlarunclassified
“…These numbers justify the presence of extensive literature related to chest injuries where the difference in epidemiology and clinical outcomes between adults and children has been well documented [23] as well as the effects between patients with flail chest vs. pulmonary contusion [9]. Authors have also effectively analysed the impact of age, rib fractures [4], pulmonary contusion [13], pelvic fractures [11], intramedullary nailing [5] and the role of analgesia [7].…”
Section: Introductionmentioning
confidence: 99%
“…16,18 One retrospective study reported a prodrome of pain and acute dyspnea in 82% of emergency patients with delayed hemothorax after discharge, 17 whereas other prospective prediction studies reported that the presence of thoracic contusions alone could represent a predictive factor for delayed complications. 3,18 Age over 45 years 35 or age over 65 years 36 was also considered as a possible stand-alone predictive factor. The incidence of delayed hemothorax in the current study was slightly higher than in previous studies, which could be attributed to our prospective design, the important follow-up rate and the slightly older age of our cohort relative to previous studies.…”
Section: Discussionmentioning
confidence: 99%